The keeping dynamic balance of ecosystems Earth. (Natural and anthropogenic mechanisms) - Skowroński, Antoni (Studia Ecologiae et Bioethicae, 2004)
Article comprehends analysis of biosphere and ecosystem notions and shows the importance of the dynamic balance of ecosystems such processes: physic-chemical cases sustaining life on the Earth and anthropogenic threats of the social and natural environment.